2003
DOI: 10.1016/s1090-9516(02)00108-6
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the factors that influence employee participation in Europe

Abstract: The goal of this study was to identify the determinants of direct employee participation in organizations across Europe. Some factors were predicted to be related to levels of participation in general, namely, competition, sector, the pursuit of a differentiation strategy based on either quality or service, and indirect participation. Two additional factors were expected to be differentially related to two forms of direct participation: consultation and delegation. These factors were organizational size and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 18 publications
3
50
1
4
Order By: Relevance
“…However, Cabrera et al (2003) found that the services sector (e.g. hospitality and tourism) practised significantly higher levels of employee participation than firms in the manufacturing (production-oriented) sector.…”
Section: Economic Sector and Participationmentioning
confidence: 93%
See 3 more Smart Citations
“…However, Cabrera et al (2003) found that the services sector (e.g. hospitality and tourism) practised significantly higher levels of employee participation than firms in the manufacturing (production-oriented) sector.…”
Section: Economic Sector and Participationmentioning
confidence: 93%
“…Hyman and Mason 1995; Lawler, Mohrman and Ledford 1995, as cited in Cabrera et al 2003). Size and participation were positively related as larger organisations were likely to introduce more innovative and participative practices, compared with smaller organisations.…”
Section: Size and Participationmentioning
confidence: 98%
See 2 more Smart Citations
“…As Maniha (1975) observed, particularism is a matter of degree, even in bureaucratic contexts, but some societies are more particularistic than others. The management of culture is marked by low levels of participation (Cabrera, Ortega and Cabrera 2003;Gill, 1993); there is a comparatively low number of engineers 3 , and widespread evidence of poor managerial practices of planning and systematization .…”
Section: History Management and Organizationmentioning
confidence: 99%